The Motive of Educational Accomplishment of the Secondary School Students, and its Relation with Self-concept and Scholastic Achievement A Field Study at Damascus Schools - ALfoal , Mohammad; Naser , Amane (Latakia University Journal - Arts and Humanities Sciences Series, 2016)
The student’s success depends on how much amount he / she has of motivation for educational accomplishment; where the stronger the motivation is, the better the student’s educational accomplishment gets, and on the contrary, the student’s endeavor decrease, his / her tendency to accomplish goes down and he / she starts to neglect his / her scholastic achievement when his / her motivation for accomplishing drops. And on return, the educational accomplishment motive is considered as an important factor among the factors that enhance the positive concept of self. The current research aims to get familiar with the relation between the educational accomplishment motive and each of self-concept and scholastic achievement. This current research has included some of high school students from Damascus schools whose number was about (1377) males and females: where (673) of them males and (704) females, (676) of them with scientific branch and (701) with literary branch. The researcher has used two scales; one of them is of the educational accomplishment motive that is prepared by Farooqe Abd-Alfattah, and the other is Tennesse’s scale of self-concept. In order to study the differences and the correlations and in order to answer the research inquiries, the descriptive method has been applied with a scanning way and with correlations. The research has included secondary class students, and this selection was randomly. After the extractionof honesty and constancy resultant from applying both scales, the researcher has come to the following results: 1. The educational accomplishment level of the research’s sample was medium. 2. The self-concept level degree (as whole) of the research’s sample was medium except of that the personal self-concept level was high. 3. There is difference of statistical indication between the averages of research sample degrees on the scales of educational accomplishment motive and self-concept according to gender variable. This was in the advantage of the bigger average which is females. 4. There is difference of statistical indication between the averages of research sample degrees on the scales of educational accomplishment motive and self-concept according to specialty variable. This was in the advantage of the bigger average which is literary branch students. 5. There is a positive correlation of a statistical indication between the educational accomplishment motive and each of self-concept and scholastic achievement.